2021
DOI: 10.3390/vaccines9121421
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire Survey of Possible Association of Allergic Diseases with Adverse Reactions to SARS-CoV-2 Vaccination

Abstract: To protect against COVID-19, SARS-CoV-2 vaccines have been widely used. Besides anaphylaxis, some less severe adverse effects may occur at higher frequencies. It remains unclear whether present or past histories of allergic diseases exert effects on local and systemic reactions. We conducted a questionnaire survey among workers in our hospital. We analyzed the adverse effects occurring after the first and second doses of the Pfizer–BioNTech vaccine in 955 subjects. The presence or absence of local injection re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
2
0
0
Order By: Relevance
“…The frequency was similar to that in the placebo group (33.6% and 33.0%, respectively) and was consistent with our results (30.4%) [38]. The higher frequency of adverse reactions in those with allergic diseases was consistent with previous reports on adults [39]. It has been suggested that individuals with allergic diseases, such as asthma, who are potentially susceptible to COVID-19 [8; [25][26][27][28][29], may experience more adverse reactions after BNT162b2 vaccination.…”
Section: Discussionsupporting
confidence: 93%
“…The frequency was similar to that in the placebo group (33.6% and 33.0%, respectively) and was consistent with our results (30.4%) [38]. The higher frequency of adverse reactions in those with allergic diseases was consistent with previous reports on adults [39]. It has been suggested that individuals with allergic diseases, such as asthma, who are potentially susceptible to COVID-19 [8; [25][26][27][28][29], may experience more adverse reactions after BNT162b2 vaccination.…”
Section: Discussionsupporting
confidence: 93%
“…The frequency was similar to that in the placebo group (33.6 and 33.0%, respectively) and was consistent with our results (30.4%) [ 39 ]. The higher frequency of adverse reactions in those with allergic diseases was consistent with previous reports on adults [ 40 ]. It has been suggested that individuals with allergic diseases, such as asthma, who are potentially susceptible to COVID-19 [ 8 , 25 29 ], may experience more adverse reactions after BNT162b2 vaccination.…”
Section: Discussionsupporting
confidence: 92%